IMPLEMENTASI KURIKULUM 2013 DAN PROGRAM LINK AND MATCH PADA SEKOLAH MENENGAH KEJURUAN (STUDI KASUS DI SMK NEGERI 1 SUTERA KABUPATEN PESISIR SELATAN) - Riza Desriandi; Yepi Herpanda; Nurhizrah Gistituati; Alwen Bentri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
Vocational high school (SMK) is secondary education that prepares students to work according to their respective fields. The SMK curriculum's development is needed to improve the quality of graduates who have the potential to work according to the interests and needs of society. Therefore, the SMK curriculum must be in line with what is needed by the world of work, not adjusted to government policies. In the SMK curriculum, we recognize the term link and match as a form of curriculum alignment with the demands of the business and industrial world (DUDI). However, implementing the 2013 Curriculum policy and link and match encountered problems, namely the teaching factory program. This study aimed to see the implementation of the 2013 curriculum and the link-and-match program implemented by schools, teachers, and students at SMK Negeri 1 Sutera. The research used is qualitative research where the data sources or respondents are school principals, teaching and education staff, and parties involved in curriculum implementation. Data collection techniques are observation, interviews, and studies. Data analysis used an interactive model. Data validity used data triangulation. The results of the study show that: 1) In general, the implementation of the 2013 curriculum at SMK Negeri 1 Sutera in the program has been going well but needs to be improved in the PPK and GLS programs, 2) the implementation of learning in the classroom still needs to be improved because there are still several teachers, especially in using learning methods are still teacher-centered, 3) the implementation of street vendors, teaching factories, and Special Job Fairs has not been implemented optimally because there are differences between KD and implementation in the field.